Isogenic human pluripotent stem cell pairs reveal the role of a KCNH2 mutation in long-QT syndrome - Bellin, Milena; Casini, Simona; Davis, Richard P.; D'Aniello, Cristina; Haas, Jessica; Ward-Van Oostwaard, Dorien; Tertoolen, Leon G. J.; Jung, Christian B.; Elliott, David A.; Welling, Andrea; Laugwitz, Karl-Ludwig; Moretti, Alessandra; et al. (EMBO Journal, 2013)
Patient-specific induced pluripotent stem cells (iPSCs) will assist research on genetic cardiac maladies if the disease phenotype is recapitulated in vitro. However, genetic background variations may confound disease traits, especially for disorders with incomplete penetrance, such as long-QT syndromes (LQTS). To study the LQT2-associated c.A2987T (N996I) KCNH2 mutation under genetically defined conditions, we derived iPSCs from a patient carrying this mutation and corrected it. Furthermore, we introduced the same point mutation in human embryonic stem cells (hESCs), generating two genetically distinct isogenic pairs of LQTS and control lines. Correction of the mutation normalized the current (I Kr) conducted by the HERG channel and the action potential (AP) duration in iPSC-derived cardiomyocytes (CMs). Introduction of the same mutation reduced I Kr and prolonged the AP duration in hESC-derived CMs. Further characterization of N996I-HERG pathogenesis revealed a trafficking defect. Our results demonstrated that the c.A2987T KCNH2 mutation is the primary cause of the LQTS phenotype. Precise genetic modification of pluripotent stem cells provided a physiologically and functionally relevant human cellular context to reveal the pathogenic mechanism underlying this specific disease phenotype. © 2013 European Molecular Biology Organization.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Gene targeting; HERG; Human embryonic stem cells; Induced pluripotent stem cells; Long-QT syndrome